Vagal response in cryoballoon ablation of atrial fibrillation and autonomic nervous system: Utility of epicardial adipose tissue location. Issue 4 (24th April 2017) - Yanagisawa, Satoshi; Inden, Yasuya; Mizutani, Yoshiaki; Fujii, Aya; Kamikubo, Yosuke; Kanzaki, Yasunori; Ando, Monami; Funabiki, Junya; Murase, Yosuke; Takenaka, Masaki; Otake, Noriaki; Hattori, Tetsuyoshi; et al.
Abstract: Background: Mechanism and effects of vagal response (VR) during cryoballoon ablation procedure on the cardiac autonomic nervous system (ANS) are unclear. The present study aimed to evaluate the relationship between VR during cryoballoon catheter ablation for atrial fibrillation and ANS modulation by evaluating epicardial adipose tissue (EAT) locations and heart rate variability (HRV) analysis. Methods: Forty‐one patients with paroxysmal atrial fibrillation (11 with VR during the procedure and 30 without VR) who underwent second‐generation cryoballoon ablation were included. EAT locations and changes in HRV parameters were compared between the VR and non‐VR groups, using Holter monitoring before ablation, immediately after ablation and one month after ablation. Results: The total EAT volume surrounding the left atrium (LA) in the VR and non‐VR groups was 29.0±18.4 cm 3 vs 27.7±19.7 cm 3, respectively ( p =0.847). The VR group exhibited greater EAT volume overlaying the LA‐left superior pulmonary vein (PV) junction (6.1±3.6 cm 3 vs 3.6±3.3 cm 3, p =0.039) than the non‐VR group. HRV parameters similarly changed following ablation in both the groups. EAT volume overlaying LA‐right superior PV junction was significantly correlated with the relative changes in root‐mean‐square successive differences ( r =−0.317, p =0.043) and high frequency ( r =−0.331, p =0.034), immediately after the ablation. Conclusions: Changes in HRV parameters following ablation were similarly observed in both the groups. EAT volume on the LA‐PV junction is helpful for interpretation of VR occurrence and ANS modulation.